CODE MIXING USED BY THE TEACHER AND THE STUDENTS IN CLASSROOM INTERACTION AT MTs MODERN TARBIYAH TAKALAR ISLAMIC BOARDING SCHOOL - Indrahayu; Mardiana; Nur Asik (ELTIES : English Language Teaching for EFL Learners, 2022)
This study aims 1). To show the types of code-mixing applied by the teacher and students when interacting in the English learning process in Class VII.D MTs Modern Tarbiyah Takalar Islamic Boarding School. 2). To describe the perceptions of students and teachers about code-mixing that is applied when interacting in the process of learning English in Class VII. D MTs Modern Tarbiyah Takalar Islamic Boarding School. This study used a qualitative descriptive design. Data were taken from classroom observations, interviews, and recorders with teachers and students when interacting during the learning process, to determine the type of code-mixing used by teachers and students in the English learning process and to obtain data about student and teacher perceptions of code-mixing. Data were analyzed based on the type of code-mixing according to Hoffman's theory. The results showed that there were three types of code-mixing consisting of 60 utterances, 53 utterances for intra-sentential code-mixing, 3 for intra-lexical code-mixing, and 4 for involving changes in pronunciation. There is a perception of students and teachers in the use of code-mixing in the learning process. For the teacher perception, that code-mixing can train students' ability to speak English, students can define new vocabulary, and make it easier for students to understand the content of learning. The Students perceived that the use of code-mixing in the English teaching and learning process is required to help them understand the content of learning so that the teaching and learning process can run well.